Formulation of Takokak Leaf Powder (Solanum torvum Swartz.) with Cinnamon and Palm Sugar as a Herbal Drink - Ginitri, A.A. Bulan; Agung, Ida Ayu Mirah (Jurnal Pijar Mipa, 2025)
Public health is increasingly becoming a major concern, especially in efforts to prevent disease through healthier and more natural consumption patterns. Herbal drinks have become one of the most widely developed alternatives because of their health benefits. Various medicinal plants have been traditionally used in folk medicine, including takokak leaves (Solanum torvum Swartz.), cinnamon (Cinnamomum spp.), and palm sugar (Arenga pinnata). Takokak leaves are known to contain bioactive compounds with potential antioxidant properties, while cinnamon and palm sugar contribute to enhancing palatability while enriching bioactive compounds. This study aims to formulate takokak leaf powder (Solanum torvum Swartz.) with cinnamon and palm sugar as a herbal beverage and evaluate its functional potential. This study is an experimental study with a completely randomized design (CRD) comprising six treatment combinations and one control. The results showed that the addition of cinnamon and palm sugar to the takokak leaf herbal beverage significantly affected the levels of flavonoids, phenols, tannins, and IC50. Flavonoid levels ranged from 6.38 to 9.71 mg/100g, phenolic content ranged from 4.67 to 6.49 mg/100g, tannin content ranged from 3.74 to 7.19 mg/100g, and IC50 values ranged from 19,293.34 to 42,290.50 ppm. The results also showed that all positive treatments contained alkaloid and saponin compounds. Based on the hedonic sensory test results, treatment P1 (2% cinnamon and 3% palm sugar) received the highest preference score compared to other treatments based on the parameters of color, aroma, taste, viscosity, and overall acceptance. These findings indicate the potential of takokak herbal beverage formulations as a source of natural antioxidants that are sensorially acceptable. Further research is recommended to evaluate takokak leaf herbal beverages with the addition of cinnamon and palm sugar in vitro and in vivo.